Cirogrillus w Liber de rerum natura Tomasza z Cantimpré - Morta, Krzysztof (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
This article analyses the problem of the cirogrillus, an animal described in the encyclopaedia Liber de natura rerum of Thomas of Cantimpré. The article’s author looks more closely at the codex of this work (from the fifteenth century) from the University Library in Wrocław, where next to the description there is also a miniature image depicting this animal. The first reference to the cirogrillusis found in the Septuagint, the Greek translation of the Old Testament from the third century, where the Hebrew term shaphan is translated using the otherwise unknown zoonym χοιρογρύλλιος. The article’s author notes that this could testify to the fact that this animal was mainly associated with the Alexandrian environment, where it could have originated together with other exotic animals which were imported into Alexandria from southern Africa for Ptolemy Philadelphus. In the remaining parts the Greek oikumene was unknown. From this there also arose problems with identifying in later biblical exegeses the actual name of the animal (choerogrillius- cirogrillus- corcodillus). Cherogrilos is variously identified, mostly as a hare, or hedgehog, which is more a result of misunderstanding than any deeper attributive enquiry. Further misunderstanding has emerged in the appearance of a description of the cherogrilos as an animal bearing the features of a hare and hedgehog (small, timid, covered with spines), that is a weak and defenceless animal which seeks protection from predators in rocky areas. But Thomas’s description stands out against these in its dissimilarity. For in his Liber de natura rerum we find an image of an animal which is indeed small, but also exceptionally dangerous, predatory, and deadly towards other animals. This isolated description was taken from the tradition of Hesychius (fifth century). In the Greek exegesis in the commentary on the Book of Leviticus the cherogrilos was described in a very similar way to what is found in Thomas’s work. This animal, together with other unpleasant creations of Hesychius, were used by Hesychius to characterise Jewish scholars and the Pharisees in a very negative manner. In alluding to the cherogrilos, a harmful, even deadly animal, in his references to Jewish people, he wanted to underline what he saw as the harmfulness of their views and knowledge. From the various pieces of information which were circulating on the topic of the cherogrilos he chose the ones which best suited his context. The article’s author suggests that in this instance there existed exaggerated negative views of the hedgehog. We cannot conclude that this was also influenced by the characteristics of the marine counterparts of the hare or hedgehog and their dangerous properties. Thomas of Cantimpré made use in his encyclopaedia of this sinister description of the cherogrilos, which he could have taken directly from Rabanus Maurus, who in his work Enarratio super Deuteronomium relied on the exegesis of Hesychius.
Keywords: beasts; Thomas of Cantimpré; cirogrillus